ANTROPOLOGIS TENTANG TRAFFICKING TKW DI MALAYSIA: ANTARA ADA DAN TIADA - Astuti, Tri Marhaeni Pudji (Forum Ilmu Sosial, 2008)
Trafficking has existed since the period of kingdoms in Java, going on to the colonialism period, andto the present time. Its meaning is broadening beyond human trading into the matters related to violence,blackmailing, and forcing. Trafficking happens not only within one specific area, but has crossed theborder of countries, indicating the existence of an international net. The mushrooming of trafficking isdue to weak law and political commitment of the concerning countries. Moreover, the bilateral talk tobanish trafficking has not been maximally conducted. The actors of trafficking vary from man-powerbrokers, agents, taxi drivers, and even officers (of transmigration and police offices). Trafficking happens invarious places ranging from luxurious spots or starred-hotels to plantations and areas which accommodatea lot of migrants. The victims are usually in so unfavorable bargaining positions that they are muchdependent on those traffickers. This dependency is the impact of imbalanced gender relation. Based onsome existing cases, it is indicated that the women’s lack of power, strength, information, and educationare often misused by the traffickers to take them as their preys. That is why empowering migrant womenis very crucial. One of the ways is empowering them through their realization that this need comes fromtheir own selves, not from any force outside. Besides, there should be strong commitment from the stateto seriously implement the law against any traffickers. Cooperation between the concerning countriesare also needed, for instance by issuing common regulations to banish trafficking.Keywords: Trafficking, migrant women, receiving country, sending country, trafficker